DEVELOPMENT OF LEARNING VIDEOS BASED ON ADOBE PREMIERE PRO FOR ELEMENTARY SCHOOL STUDENTS - Revita Revita; Bagus Amirul Mukmin; Endang Sri Mujiwati (Universitas Labuhanbatu, 2024)
The background of this research is the observation of class IV, at SDN Tiron 3 teachers are not optimal in using learning media to convey material, the low motivation of a teacher so that students' interest in learning is low and the learning process is boring. The formulation of the problem of this research: How is the validity, practicality, effectiveness of learning video based on Adobe Premiere Pro on energy resources for fourth grade students at SDN Tiron 3? In this study using the type of research and development (Research and Development). The model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) developed by Sugiyono. The research subjects were fourth grade students at SDN Tiron 3. The results of the study (1) The results of the validation of media experts obtained a percentage of 90% and material experts 88%. The average level of validity score is 89%, it can be stated that it is very valid. (2) The results of the teacher's response questionnaire obtained a percentage of 96.66% and the student response questionnaire was 90%. The average level of practicality gets a score of 93.33%, it can be stated that it is very practical. (3) The results of the limited trial obtained a percentage of 92.59% and 90% of the wide trial. The average level of effectiveness gets a score of 91,30%, so it can be declared very significant.Keywords: Development, learning videos, adobe premiere pro, energy resources materials.The background of this research is the observation of class IV, at SDN Tiron 3 teachers are not optimal in using learning media to convey material, the low motivation of a teacher so that students' interest in learning is low and the learning process is boring. The formulation of the problem of this research: How is the validity, practicality, effectiveness of learning video based on Adobe Premiere Pro on energy resources for fourth grade students at SDN Tiron 3? In this study using the type of research and development (Research and Development). The model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) developed by Sugiyono. The research subjects were fourth grade students at SDN Tiron 3. The results of the study (1) The results of the validation of media experts obtained a percentage of 90% and material experts 88%. The average level of validity score is 89%, it can be stated that it is very valid. (2) The results of the teacher's response questionnaire obtained a percentage of 96.66% and the student response questionnaire was 90%. The average level of practicality gets a score of 93.33%, it can be stated that it is very practical. (3) The results of the limited trial obtained a percentage of 92.59% and 90% of the wide trial. The average level of effectiveness gets a score of 91,30%, so it can be declared very significant.Keywords: Development, learning videos, adobe premiere pro, energy resources materials.